Development of a Survey Instrument to Gauge Students’ Problem-Solving Abilities - Marx, Jeffrey; Cummings, Karen; Singh, Chandralekha; Sabella, Mel; Rebello, Sanjay (2010 Physics Education Research Conference, 2010)
In this paper we discuss the early stages of development of a survey instrument to assess students' problem-solving abilities in a first-term, undergraduate, calculus-based physics course. Specifically, we present our motivation for the development of such a survey, details of a preliminary version of the survey, and some sample items. © 2010 American Institute of Physics.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/150-977-856-086-461, pop00163 tex.number: [object Object]
Keywords: Problem-solving; assessment; dept.phy; introductory physics

Beta-Test Data On An Assessment Of Textbook Problem Solving Ability: An Argument For Right∕Wrong Grading? - Cummings, Karen; Marx, Jeffrey D.; Singh, Chandralekha; Sabella, Mel; Rebello, Sanjay (2010 Physics Education Research Conference, 2010)
We have developed an assessment of students' ability to solve standard textbook style problems and are currently engaged in the validation and revision process. The assessment covers the topics of force and motion, conservation of momentum and conservation of energy at a level consistent with most calculus-based, introductory physics courses. This tool is discussed in more detail in an accompanying paper by Marx and Cummings. [1] Here we present preliminary beta-test data collected at four schools during the 2009/2010 academic year. Data include both pre- and post-instruction results for introductory physics courses as well as results for physics majors in later years. In addition, we present evidence that right/wrong grading may well be a perfectly acceptable grading procedure for a course-level assessment of this type. © 2010 American Institute of Physics.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/136-768-475-813-84X, pop00255 tex.number: [object Object]
Keywords: Problem solving in physics; assessment; dept.phy; introductory physics; right/wrong grading